Parental involvement in enhancing the achievement of taekwondo athletes - Katerina Davi; Rivan Saghita Pratama; Indra Ramadhan; Wiga Nurlatifa Romadhoni (Universitas Sriwijaya, 2025)
Research Problems: Parental involvement is a crucial factor in supporting the development and achievement of athletes, including those in Taekwondo. Parents’ support, in the form of motivation, accompaniment, and facilities, plays an important role in shaping athletes’ confidence and performance. However, the level of involvement often varies, making it necessary to investigate further the role of parents in the process of fostering athletic achievement. Research Objectives: This study aims to describe the forms of parental involvement in supporting the improvement of Taekwondo athletes’ performance. Methods: The study employed a descriptive qualitative approach with participants consisting of coaches, athletes, and parents from the Koryo Club and Lembah Cobra Taekwondo Dojangs in Pekalongan Regency. Data were collected through observation, in-depth interviews, and documentation, using interview guidelines, observation sheets, and supporting documents as instruments. Data were analysed using source and method triangulation to ensure validity and provide a comprehensive understanding. Results: The findings indicate that parental involvement manifests in four main aspects: motivational (encouragement, praise, and support during failure), logistical (providing facilities and training needs), emotional (accompanying athletes during training and competitions), and educational (family communication regarding the athlete’s development). This involvement positively contributes to athletes’ motivation, confidence, and achievement. Conclusion: Parental involvement plays a significant role in enhancing Taekwondo athletes’ performance. Comprehensive parental support not only strengthens children’s motivation but also creates a more conducive environment for athletic development.